Boko Haram and Niger Delta Avengers: unraveling the greed-need-creed spectrum in Nigeria’s security-development nexus - David, James Ojochenemi (Frontiers in Political Science, 2025)
IntroductionThis study revisits the debate surrounding the security-development nexus by analyzing the motivations and impacts of two key insurgent groups: Boko Haram and the Niger Delta Avengers in Nigeria. It seeks to understand how socio-economic, ideological, and governance-related factors contribute to the existence of both groups in similar and/or different ways, and the overall implications for sustainable peace and development in Nigeria.Methodological and theoretical frameworksThe research employs a qualitative methodology, utilizing both primary and secondary data sources, including academic literature, policy reports, media analysis, and semi-structured interviews with experts. Thematic analysis is conducted within the conceptual framework of the “Greed, Need, and Creed Spectrum,” which categorizes the drivers of conflict into economic incentives (greed), socioeconomic deprivation (need), and ideological or religious motivations (creed). In addition, this study combines the analytical potential of the Rational Choice and Root Cause theories (2RCs) to illuminate how the greed-need-creed spectrum can help in deepening the understanding of the security-development nexus in Nigeria, especially regarding the two insurgencies in question.ResultsFindings reveal a complex interplay between economic inequality, underdevelopment, and governance deficits across Nigeria’s geopolitical zones. Boko Haram’s insurgency is primarily fueled by religious ideology and socio-political exclusion in the Northeast, while the Niger Delta Avengers capitalize on environmental grievances and resource control claims to justify economically motivated sabotage. Meanwhile, socioeconomic deprivation serves as a foundational grievance that enables both groups to mobilize support. Informed by the 2RCs, the study highlights that responses rooted solely in militarization fail to address the deeper structural causes of these similar but different insurgencies, considering relevant contextual factors. It re-echoes the calls for a shift toward integrated policy approaches that target the root causes of insecurity, including poor governance, youth unemployment, and environmental injustice, while considering the regional peculiarities of both insurgencies and like-minded groups.Conclusion and recommendationThis study essentially underscores how the Greed-Need-Creed framework provides a valuable perspective necessary for crafting multidimensional counter-insurgency strategies that align national security with human development objectives, including participatory governance, localized economic development, and community-driven deradicalization programs.